The apple 14-3-3 gene MdGRF6 negatively regulates salt tolerance - Zhu, Yuqing; Kuang, Wei; Leng, Jun; Wang, Xue; Qiu, Linlin; Kong, Xiangyue; Wang, Yongzhang; Zhao, Qiang (Frontiers in Plant Science, 2023)
The 14-3-3 (GRF, general regulatory factor) regulatory proteins are highly conserved and are widely distributed throughout the eukaryotes. They are involved in the growth and development of organisms via target protein interactions. Although many plant 14-3-3 proteins were identified in response to stresses, little is known about their involvement in salt tolerance in apples. In our study, nineteen apple 14-3-3 proteins were cloned and identified. The transcript levels of Md14-3-3 genes were either up or down-regulated in response to salinity treatments. Specifically, the transcript level of MdGRF6 (a member of the Md14-3-3 genes family) decreased due to salt stress treatment. The phenotypes of transgenic tobacco lines and wild-type (WT) did not affect plant growth under normal conditions. However, the germination rate and salt tolerance of transgenic tobacco was lower compared to the WT. Transgenic tobacco demonstrated decreased salt tolerance. The transgenic apple calli overexpressing MdGRF6 exhibited greater sensitivity to salt stress compared to the WT plants, whereas the MdGRF6-RNAi transgenic apple calli improved salt stress tolerance. Moreover, the salt stress-related genes (MdSOS2, MdSOS3, MdNHX1, MdATK2/3, MdCBL-1, MdMYB46, MdWRKY30, and MdHB-7) were more strongly down-regulated in MdGRF6-OE transgenic apple calli lines than in the WT when subjected to salt stress treatment. Taken together, these results provide new insights into the roles of 14-3-3 protein MdGRF6 in modulating salt responses in plants.